2009
DOI: 10.1002/pbc.22081
|View full text |Cite
|
Sign up to set email alerts
|

Medical, psychological, cognitive and educational late‐effects in pediatric low‐grade glioma survivors treated with surgery only

Abstract: "Surgery-only" LGG survivors may be more affected by their tumor and its resection than previously appreciated. A prospective study is needed to address this survivor population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
4
49
2
Order By: Relevance
“…In our opinion, several factors increase the strength of the present study; firstly, separate studies in survivors of low incidence cancers are rare but needed to recognize late effects specific for each cancer type and its treatment. As opposed to ALL and brain tumors, AML, IA and WT have only rarely been subject to separate studies of social/ psychosocial outcomes [10,[24][25][26][27][28][29]. Also, the treatment in the Nordic countries is based upon the same protocols, which provides the opportunity to study a representative sample size.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our opinion, several factors increase the strength of the present study; firstly, separate studies in survivors of low incidence cancers are rare but needed to recognize late effects specific for each cancer type and its treatment. As opposed to ALL and brain tumors, AML, IA and WT have only rarely been subject to separate studies of social/ psychosocial outcomes [10,[24][25][26][27][28][29]. Also, the treatment in the Nordic countries is based upon the same protocols, which provides the opportunity to study a representative sample size.…”
Section: Discussionmentioning
confidence: 96%
“…Mackie et al found that mean overall work and educational performance in 35 WT survivors was similar to that of age-matched controls from local hospitals [24]. Studies on psychosocial outcomes among survivors of IA have mainly addressed quality of life and some social outcomes in relatively small samples [10,[27][28][29]. The latter studies have used various comparison groups which makes it difficult to ascertain if IA survivors have a social functioning different from the general population.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, survivors of pilocytic astrocytomas commonly suffer long-term sequelae related to disease and treatment. 913 Thus, a better understanding of pilocytic astrocytoma biology is needed to guide the development of new therapies to decrease morbidity and improve survival.…”
mentioning
confidence: 99%
“…Studies on long-term functional outcomes are conflicting, with some suggesting patients perform well [5,6] whereas others report higher than expected rates of cognitive and psychosocial difficulties [7-10]. Variability in functioning occurs in patients treated with surgery [6,11,12] as well as those treated with chemotherapy [13,14], irradiation [13,15], or combination.…”
mentioning
confidence: 99%